Предмет: Алгебра,
автор: danillinkov034
Упрастите выражение.
1)(4a²-3b)2b-(3a²-4b)3b
2)3(2x-1)-5(x-3)+6(3x-4).
Помогите прашу ПЖ.
Ответы
Автор ответа:
0
Объяснение:
● 1. (4a^2-3b)2b-(3a^2-4b)3b= 8a^2b-6b^2-(9a^2b-12b)=
=8a^2b-6b^2-9a^2b+12b= -a^2b-6b^2+12b=
= -6b^2-a^2b+12b |×(-1)=
=6b^2-a^2b+12b
● 2. 3(2x-1)-5(x-3)+6(3x-4)=6x-3-5x+15+18x-24=19x-18
Автор ответа:
0
Скачай Photomath. Допоможе з будь яким виразом
Похожие вопросы
Предмет: Русский язык,
автор: Ludonchica
Предмет: Математика,
автор: oksanavika
Предмет: Математика,
автор: specterx
Предмет: Литература,
автор: maksosipow